Molecular characterization of CYP1B1 in primary congenital glaucoma in Pakistan - Atif, Amin Baig; Yasrul Izad, Abu Bakar; Khan, M.U. (2017)
Primary congenital glaucoma (PCG) is the foremost cause of blindness in children. In PCG the optic nerve damage and permanent loss of vision occurs because of developmental defects of trabecular meshwork of the eye. The mode of inheritance of PCG is mostly autosomal recessive, so, its incidence is higher in residents where consanguinity is common. CYP1B1 is a major contributing gene for PCG. The present study aimed to investigate the mutational spectrum of the CYP1B1 in Pakistani patients affected with PCG. This study comprised of 35 unrelated individuals clinically diagnosed with PCG by standard ophthalmological examinations. Genomic DNA was extracted from blood samples of these patients and screened for mutations in CYP1B1 by amplifying itsall coding regions with specifically designed primers. PCR products were purified and Sanger sequencing was done by using BigDye terminators and capillary electrophoresis. Sequencing analysis revealed one mutation, c.1169 G>A in exon 3 of CYP1B1 gene. This missense mutation replaces Arginine with Histidine at codon 390. This homozygous mutation was observed in (7 patients) 20% of the PCG patients enrolled in the study. In addition two missense sequence variants c.1294G>C (2 patients), c.1358A>G (4 patients) and a synonymous variant c.1347T>C (18 patients) were also seen in the present study. The results of the current study reflect that CYP1B1 mutation is one of the cause of primary congenital glaucoma in Pakistani patients.